2015
DOI: 10.1371/journal.pone.0122112
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Knowledge, Attitudes, Behaviour and Health Care Experiences on the Prevention, Detection, Management and Control of Hypertension in Colombia: A Qualitative Study

Abstract: Hypertension is a leading cause of premature death worldwide and the most important modifiable risk factor for cardiovascular disease. Effective screening programs, communication with patients, regular monitoring, and adherence to treatment are essential to successful management but may be challenging in health systems facing resource constraints. This qualitative study explored patients’ knowledge, attitudes, behaviour and health care seeking experiences in relation to detection, treatment and control of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
108
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(135 citation statements)
references
References 18 publications
(20 reference statements)
14
108
2
11
Order By: Relevance
“…Such finding is corroborated by studies carried out in Colombia 23 , United States 24 and Brazil 15 . In the national study, for instance, individuals with SAH who had access to health plans were nearly three times more likely to attend medical consultations 15 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Such finding is corroborated by studies carried out in Colombia 23 , United States 24 and Brazil 15 . In the national study, for instance, individuals with SAH who had access to health plans were nearly three times more likely to attend medical consultations 15 .…”
Section: Discussionsupporting
confidence: 61%
“…Based on clinical practice and literature evidence 19,23 , it is believed that the presence alone of individuals at consultations is not enough for compliance with the treatment and for the reduction of BP rates. From this perspective, a study carried out in Colombia evidenced that individuals with SAH valued the work method applied, the activities developed at the health unit, the quality of the care provided and the quality of interpersonal relationships and communication established between professional and patient, as the main factors that led patients to stick to consultations 23 . In this sense, in order to increase rates of use of routine consultations in PC, healthcare professionals should consider, during their practice, the aforementioned aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Those completed so far reveal complex pictures relating to both demand for treatment, influenced by cost of drugs and by how hypertension – a chronic, asymptomatic, but hazardous condition – is conceptualized, and by supply of trained health professionals and medicines [34, 35]. Other data from the Environmental Profile of a Community’s Health study (EPOCH), nested within PURE, also provide insights.…”
Section: Discussionmentioning
confidence: 99%
“…Usually patients who are diagnosed with hypertension are prescribed medications to manage their disease, yet they know only a little about it and its complications. Effective screening methods, better communication with patients, frequent check-ups and compliance to drugs and healthy practices are all essential to achieve success in management but unfortunately these are actually real challenges [8]. Moreover studies showed that many of the hypertensive patients forget to take the prescribed medication occasionally thus emphasizing the great role of communication strategies of health professionals and the necessity of improving doctor-patient relationship [9].…”
Section: Introductionmentioning
confidence: 99%